A novel fold for the factor H-binding protein BbCRASP-1 of Borrelia burgdorferi - Cordes, Frank; Roversi, Pietro; Kraiczy, Peter; Simon, Markus M.; Brade, Volker; Jahraus, Oliver; Wallis, Russell; Skerka, Christine; Zipfel, Peter F.; Wallich, Reinhard; Lea, Susan M. (Nature structural & molecular biology, 2005)
Borrelia burgdorferi, a spirochete transmitted to human hosts during feeding of infected Ixodes ticks, is the causative agent of Lyme disease. Serum-resistant B. burgdorferi strains cause a chronic, multisystemic form of the disease and bind complement factor H (FH) and FH-like protein 1 (FHL-1) on the spirochete surface. Here we report the atomic structure for the key FHL-1- and FH-binding protein BbCRASP-1 and reveal a homodimer that presents a novel target for drug design.
Gesehen am 07.06.2021